Pemanfaatan Sistem Penyaringan Air Buangan Air Conditioning (AC) Sebagai Suplai Pengairan Pada Tanaman: Pemanfaatan Sistem Penyaringan Air Buangan Air Conditioning (AC) Sebagai Suplai Pengairan Pada Tanaman - Latifa Mirzatika Al-Rosyid; Dwi Dita Wahyuning Tiyas; Nur Diana Rofiqoh; Roby Naufal Abiyyi (Jurnal Teknik Lingkungan, 2022)
Air Conditioning (AC) waste water has quite a lot of quantity, but usually AC waste water is directly discharged into the surrounding environment through AC waste water pipes. The objectives of the study were (1) to determine the discharge of AC waste water produced within 30 minutes and (2) to determine the effectiveness of the filter in reducing the pollutant content of AC waste water so that it is good for plant irrigation. The research was conducted by analyzing the quantity and quality of AC waste water in the CC Building, Muhammadiyah University of Jember. Parameters analyzed include hardness, pH and ammonia. One solution to sterilize AC wastewater is by using a sponge that is able to capture solids in the water before the water enters the container and activated charcoal which is considered to be able to reduce NH4 levels. One of the ingredients for making charcoal comes from coconut shells, which are relatively cheap. In addition to using coconut shell charcoal, exposure to UV rays is felt to reduce the bacteria contained in the AC water. UV light can function as a destroyer of bacteria and microorganisms so it is safe to use, both for living things and the environment. This study uses a descriptive qualitative    research with an evaluation approach which aims to determine the amount of air conditioning waste water within 30 minutes and to determine the physical and microbiological quality of AC waste water by analyzing the data and comparing it with the Minister of Health Regulation No. 32 of 2017 concerning Health Quality Standards for Sanitation, Swimming Pools, Solus Per Aqua and Public Baths. Data was collected by measuring the discharge of air conditioning, observation, interviews and documentation. The instrumentation used is a measuring cup, TDS meter, thermometer, turbidity meter, timer, sample bottle, Bunsen, alcohol and ice box. Based on the results of the examination of the quality of the AC wastewater with specifications of AC 1 PK, the results of the examination of physical and microbiological parameters that meet the requirements in accordance with the Minister of Health of the Republic of Indonesia No. 32 of 2017 concerning Health Quality Standards for Sanitation, Swimming Pools, Solus Per Aqua and Public Baths.